Sperm membrane integrity and stability after selection of cryopreserved ovine semen on colloidal solutions - Bergstein-Galan, T. G. [UNESP]; Bicudo, L. C. [UNESP]; Rodello, L. [UNESP]; Weiss, R. R.; Bicudo, S. D. [UNESP] (My University, 2018)
The aim of this study was to evaluate the effect of four methods of sperm selection, on the integrity and stability of the plasma membrane, integrity of the acrosomal membrane and spermatic morphology in frozen/thawed ovine semen. Two types of colloidal silica: colloidal silica–silane and colloidal silica–polyvinylpyrrolidone (PVP), and two aliquots: 1 and 4 ml, were used for sperm selection. Probes FITC-PSA and PI were used to measure the integrity of the plasma and acrosomal membranes. Plasma membrane stability was measured, using fluorescent probes M540 and YOPRO1. Effective reduction in the incidence of spermatozoa with acrosomal pathologies was only achieved using 1 ml colloidal silica–silane. All methods were efficient in select viable and unreacted spermatozoa. Only methods using 1 ml of silica were efficient in decrease spermatozoa stained by PI (death). Methods using silica colloidal–silane were more efficient to decrease apoptotic cells after selection when compared to silica colloidal–PVP. In conclusion, sperm selection in colloidal silica–silane and colloidal silica–PVP improved sperm quality when compared to the controls. The method using 1 ml of colloidal silica–silane is the preferred method because its effectiveness and lower cost.
Keywords: colloidal silica; sperm membranes; sperm selection